Analisis comparativo de sectores clave desde una perspectiva regional a traves de matrices de contabilidad social: Enfoques alternativos - Manuel Alejandro Cardenete (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2011)
– In this paper we extend the proportional rule to division problems with multiple references and we present a result of characterization of the weighted proportional rule. As a particular case, we analyze the problems of probability aggregation and probability updating. division problems with multiple references ; weighted proportional rule ; probability aggregation ; probability updating.
Keywords: C67; D57; R15; 330